If I know that the output of a system $$y(t) = 2e^{-3t} \cdot u(t)$$ and it's specified that the input is $$ x(t) = u(t) $$

I was trying to find the impulse response h(t).

So I solved it using Laplace transform and I got the output $$ h(t) = 2\delta(t) - [6 e^{-3t} \cdot u(t)]$$ by doing the following: $$ y(t) = x(t) * h(t) $$ therefore $$ Y(s) = X(s) \cdot H(s) $$ and by doing the laplace transform to y(t) and x(t) I optain: $$ \frac{2}{s+3} = \frac{1}{s} \cdot H(s)$$ $$ H(s) = \frac{2s}{s + 3}$$ $$ H(s) = \frac{2(s + 3) - 6}{s + 3}$$ $$ H(s) = 2 + \frac {-6}{s + 3}$$

therefore, by using the inverse Laplace transform, I got: $$ h(t) = 2\delta(t) - [6e^{-3t} \cdot u(t)] $$

Until now I think I understand it. From now on, I'd like you to correct me if I'm wrong at anything.

I know that h(t), the impulse response is the output if the input is the impulse function delta.

so I did the following:
I substituted x(t) in place of u(t) in the output equation, as x(t) = u(t) $$ y(t) = 2e^{-3t} \cdot x(t) $$ and then I applied delta as the input to get the impulse response.

$$ h(t) = 2e^{-3t} \cdot \delta(t)$$ which can be reduced to $$ h(t) = 2\delta(t) $$

I don't know what I've done wrong in that process to obtain a wrong answer in the second way.

Also, I'm pretty sure that the first impulse response is the right one because I've solved it in another way and obtained the same result (getting the step response and then differentiating it to obtain the impulse response.). It just didn't work out when I try to plug in delta.

Also, I apologize if the tags are not very accurate, but I just don't know how to categorize the question.

  • \$\begingroup\$ This step is wrong \$y(t)=2e−3t⋅x(t)\$ it should be \$y(t)=(h*x)(t)\$. Convolution \$ \neq \$ multiplication. \$\endgroup\$
    – jDAQ
    Commented Dec 10, 2019 at 17:06
  • \$\begingroup\$ Well, I know that convolution is not the same as multiplication. but all I did is that I substituted \$u(t)\$ and put \$x(t)\$ in its place, because \$x(t) = u(t)\$. \$\endgroup\$ Commented Dec 10, 2019 at 17:11
  • \$\begingroup\$ Ok, but you have to looks at the subtleties, you cannot substitute \$ u(t) \$ by \$ x(t) \$ as you did. \$ y(t)=(h*x)(t) \$ where \$ h(t) = 2\delta(t) - [6 e^{-3t} \cdot u(t)] \$, so \$ y(t) \$ would be... \$ y(t)=h(t) \$, that is the whole point of impulse responses, right? \$\endgroup\$
    – jDAQ
    Commented Dec 10, 2019 at 17:17

1 Answer 1


The step where you substituted \$x(t)\$ for \$u(t)\$ was incorrect. It's like saying "\$x(t) = 1\$, so I can substitute \$x(t)\$ for \$1\$ everywhere in my expression".

Observing that \$h(t) \star u(t) = \int_0^t h(\tau) d\tau\$ and then taking the derivative is correct, however.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.